Migration, residency and habitat utilisation by wild and cultured Japanese eels (Anguilla japonica) in a shallow brackish lagoon and inflowing rivers using acoustic telemetry. Issue 2 (20th November 2020) - Noda, Takuji; Wada, Toshihiro; Mitamura, Hiromichi; Kume, Manabu; Komaki, Takuhei; Fujita, Tsuneo; Sato, Tatsuma; Narita, Kaoru; Yamada, Manabu; Matsumoto, Akira; Hori, Tomoya; Takagi, Junichi; et al.
Abstract: This study monitored post‐release movements of 20 wild Japanese eels ( Anguilla japonica ) [mean ± S.D. 520.8 ± 92.3 mm total length (TL), 217.9 ± 146.3 g body mass (BM)] in a brackish water lagoon in northeastern Japan using acoustic telemetry to elucidate how wild Japanese eels use different river, estuary and marine environments. In addition, 12 cultured Japanese eels (TL = 578.9 ± 18.0 mm, BM = 344.9 ± 25.5 g) were released to understand the comparative behaviours of wild and cultured eels. Both types of eels were simultaneously released in the southern inner part of the lagoon in September 2016 where there are freshwater influences from a river. Following release, eight of the wild eels (40%) were largely sedentary near the released point (river mouth) and stayed at the site for overwinter. Nonetheless, several individuals showed behavioural plasticity of habitat use: three wild eels moved towards the northern part of the lagoon with stronger influence from the sea during May–July 2017. Two wild eels showed clear repeated movements from the lagoon to a river at night and returned to the lagoon by dawn for more than a week every day, and one wild eel migrated upstream for overwintering. Signals from 55% of the wild eels could be detected for more than 6 months, whereas those from all of the cultured eels were lost by December 2016, indicating a short resident time of large cultured eels (BM > 200 g) released in a brackish water area. One wild silver eel migrated to the outer sea during the ebb tide at night in November 2016, probably triggered by the decrease in water temperature (from c. 20°C to c. 13°C), and seven cultured eels similarly moved to the outer sea during October–November 2016. The results revealed the similarities ( e.g., nocturnal movements) and differences ( e.g., stay period and seasonal movements) in the behavioural characteristics of wild and cultured eels and indicated that habitat connectivity among river, estuary and coastal waters is crucial for enabling eels to efficiently utilise these productive habitats through their behavioural plasticity.